Comparison of cryoprotectants in the preservation of Theileria parva sporozoites using in vitro infectivity assay - Kimbita, E.N.; Silayo, R.S.; Jolan, T.T. (Springer, 2001)
An in vitro infectivity assay was used to examine five cryoprotectants for their suitability of preserving Theileria parva sporozoites. All five were capable of preserving T. parva sporozoites through freezing, the optimal concentrations being 7.5 percent for glycerol, 5 percent for dimethyl sulphoxide (DMSO), poly (vinylpyrrolidone) (PVP) and poly(ethylene glycol) (PEG), and 2.5 percent for hydroxyethyl starch (HES). When the five cryoprotectants were compared at their optimal concentrations, using a modification of the standard method of stabilate preparation, glycerol was significantly better than the others (p<0.0.5). Measurement of the effects of each cryoprotectant on the osmolality of the media revealed that glycerol and DMSO elevated the osmolality significantly (p<0.05). Resucitation of glycerol-preserved sporozoites required the presence of glycerol in the diluent to maintain infectivity. Studies on the effects of equilibration time in glycerol on the infectivity of sporozoites showed that those frozen immediately after mixing (2 min) were as infective as those frozen after 60 min of equilibration.